Предмет: Математика,
автор: kalybajkausar0
* (4x+1)(x+5)=(4x+1)(3x+2).
Ответы
Автор ответа:
0
Ответ:
x1 = - ; x2 =
Пошаговое объяснение:
(4x+1)(x+5)=(4x+1)(3x+2)
4 + 20x + x + 5 = 12 + 8x + 3x + 2
4 + 21x + 5 = 12 + 11x + 2
4 + 21x + 5 - 12 - 11x - 2 = 0
-8 + 10x + 3 = 0
8 - 10x - 3 = 0
8 - 2x - 12x - 3 = 0
2x * (4x+1) - 3(4x + 1) = 0
(4x + 1) * (2x - 3) = 0
4x + 1 = 0; 2x - 3 = 0
x1 = - ; x2 = или x1 = -0.25; x2 = 1.5
Автор ответа:
0
Ответ:
(4x+1)(x+5)=(4x+1)(3x+2)
(4x+1)(x+5)-(4x+1)(3x+2)=0
(4x+1)(x+5-3x-2)=0
(4x+1)(3-2x)=0
4x+1=0
x₁=-1/4
3-2x=0
x₂=1.5
ответ: x₁=-1/4 x₂=1.5
Пошаговое объяснение:
Похожие вопросы
Предмет: Английский язык,
автор: rikovapolina
Предмет: Русский язык,
автор: farzona2006
Предмет: Русский язык,
автор: Ki2008
Предмет: Алгебра,
автор: lo1144436
Предмет: Физика,
автор: yourglitterpussy